1993
DOI: 10.1021/bi00065a018
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the cAMP-dependent protein kinase catalytic subunit and its contraction upon binding the protein kinase inhibitor peptide

Abstract: Small-angle X-ray scattering and Fourier transform infrared (FTIR) spectroscopy experiments have been completed on the catalytic subunit of the cAMP-dependent protein kinase. Measurements were made both with and without the protein kinase inhibitor peptide, PKI alpha(5-22)amide. Binding of the peptide results in an overall contraction of the structure that is characterized by a decrease of 9% in radius of gyration and about 16% in the maximum linear dimension. Both the secondary structure content of the protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 21 publications
(29 reference statements)
5
77
0
Order By: Relevance
“…Our results indicate that the linker must undergo a significant conformational change upon binding C subunits to allow simultaneous contact of the cAMPbinding domains of R with the C subunits and the pseudosubstrate inhibitor sequence with the catalytic cleft of C. The backbone conformation of the pseudosubstrate sequence bound to the active site of C is very likely to be similar to that of PKI bound to C (33,34). As the pseudosubstrate region adopts this conformation, an additional conformational change could be induced within other parts of the linker region that, in turn, affect the interdomain orientation of the homodimer.…”
Section: Discussionmentioning
confidence: 87%
“…Our results indicate that the linker must undergo a significant conformational change upon binding C subunits to allow simultaneous contact of the cAMPbinding domains of R with the C subunits and the pseudosubstrate inhibitor sequence with the catalytic cleft of C. The backbone conformation of the pseudosubstrate sequence bound to the active site of C is very likely to be similar to that of PKI bound to C (33,34). As the pseudosubstrate region adopts this conformation, an additional conformational change could be induced within other parts of the linker region that, in turn, affect the interdomain orientation of the homodimer.…”
Section: Discussionmentioning
confidence: 87%
“…Although the angle formed by the two domains opens by ca. 15" between the crystal structures of the closed and open forms, data from low-angle X-ray scattering experiments of cAPK alone in solution indicated an opening of as much as 39" (Olah et al, 1993). The conformational transition between the open and closed crystal structures has been described on a structural level in great detail by Cox et al (1994).…”
Section: Pki(5-24)mentioning
confidence: 99%
“…This structural heterogeneity provides a more open conformation to allow the association of ATP even in the presence of inhibitors and substrates. Secondly, Olah et al (1993) showed by small angle X-ray scattering and Fourier transform infrared spectroscopy that a 9% decrease in the radius of gyration of the C-subunit accompanies inhibitor binding. The lack of any changes in secondary structure led these authors to propose that domain movement is the likely cause.…”
Section: Binary Atp Complex Have Equilibrated In Solutionmentioning
confidence: 99%